Kontrol Robot Manipulator Berdasarkan Pergerakan Lengan Manusia Menggunakan Electromyography - Hanifa Nur Halimah; Rizal Maulana; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
One of the rapidly growing medical innovations is the surgical robot. Robotic technology will help doctors during a surgical procedure. The advantages of robotic surgery include faster recovery, minimal scarring, and smaller incisions, resulting in a reduced risk of infection. A surgical robot, in this case, is made in the form of a manipulator robot. The manipulator robot matches the doctor's movement by reading the electromyography (EMG) signal produced by muscle contraction through the electrodes. Myoware sensor detects EMG signals of arm muscles. Myoware output signal read by Arduino Nano so that the manipulator robot moves. Robot manipulator was designed to have 4 Degree of Freedom and implemented using servo dynamixel AX-12A. The EMG signal will be filtered exponentially so that the signal is smoother. The signals that have been processed will be analyzed the amplitude to determine the type of arm movement performed. The angles detected are 00, 450, 900, 1350 and 1450. Each angle has upper limit 0.89V; 1.59V; 2.29V; 3.49V; and 5V; lower limit 0V; 0.89V; 1.59V; 2.29V; and 3,49V. the system has an accuracy of 84% in determining the type of arm movement which had taken from 5 attempts each angle by 3 subjects.